THE EFFECT OF THE BRAND IMAGE AND LIFESTYLE TOWARD THE INTEREST OF BUYING MAKEOVERS PRODUCTS AT THE COUNTER MAKEOVER BUYER AT THE SUN PLAZA - Ajeng Retno Pratiwi; Muslim Wijaya; Fadli Adnin Nasution; Sabrina Aulia Rahmah (Universitas Dharmawangsa Medan, 2022)
ABSTRACTThe purpose of this study is to understand how brand image and sexual orientation affect the amount of product purchased during counter makeover transactions at Sun Plaza Medan. This type of analysis is an associative analysis, one that connects two or more variables. 120 people make up the sample size or respondents in this study; hence, the sampling technique that will be used is random sampling. With a population of around 120 people and an error level of less than 0.01, the sample in this study consisted of about 55 people. The analysis method used in this study is multiple linear regression analysis. Data collection was carried out using observations and questionnaires during the data collection process, which combined data from the first and second stages.According to the study's findings, Brand Image data on partial tests was positively and significantly correlated with Purchase Intention. Because Brand Image has a variable tcount number of 3,753 and a fixed tcount number of 2,004, the tcount exceeds the ttable. (3.753 > 2.004) and a lower threshold for significance (0.009 0.05). With a positive and significant effect on Lifestyle's relationship to Purchase Interest, the variable Lifestyle's tcount value is 8.540, and the ttable's value is 2.004, meaning that tcount > ttable (8.540 > 2.004), and the significance level is less than 0, 05 (0.004 0.05). In parallel, Brand Image and Goodwill increased positively and significantly with respect to the amount of MakeOver products purchased at the Sun Plaza Medan counter, with an Fcount value of 62,218 and a Sig. value of 0.000b. F count > F table (62.218 > 3.16) or significance (Sig.) 5% (0.000 0.05), as appropriate.Keywords: Brand image, good health, and solid behavior are the key words.